Textkritisches zu Agatharchides von Knidos und zu Markianos von Heraklea - Lucarini, Carlo M. (Hyperboreus, 2021)
The aim of this paper is to shed new light on some passages of Agatharchides of Cnidos and Marcian of Heraclea. A new textual arrangement is proposed for ten passages of Agatharchides and eight of Marcian.